Admission eGFR predicts in-hospital mortality independently of admission glycemia and C-peptide in patients with type 2 diabetes mellitus and COVID-19. (3rd April 2023) - Infante, Marco; Pieri, Massimo; Lupisella, Santina; Mohamad, Ali; Bernardini, Sergio; Della-Morte, David; Fabbri, Andrea; De Stefano, Alberto; Iannetta, Marco; Ansaldo, Lorenzo; Crea, Angela; Andreoni, Massimo; et al.
Abstract: Objective: Type 2 diabetes mellitus (T2DM) and impaired kidney function are associated with a higher risk of poor outcomes of coronavirus disease 2019 (COVID-19). We conducted a retrospective study in hospitalized T2DM patients with COVID-19 to assess the association between in-hospital mortality and admission values of different hematological/biochemical parameters, including estimated glomerular filtration rate (eGFR), plasma glucose and C-peptide (the latter serving as a marker of beta-cell function). Methods: The study included T2DM patients with confirmed severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection who were consecutively admitted to our Institution between 1 October 2020 and 1 April 2021. Results: Patients ( n = 74) were categorized into survivors ( n = 55) and non-survivors ( n = 19). Non-survivors exhibited significantly higher median white blood cell (WBC) count, D-dimer, neutrophil-to-lymphocyte ratio, high-sensitivity C-reactive protein (hsCRP), and procalcitonin levels, as well as significantly lower median serum 25-hydroxyvitamin D [25(OH)D] levels compared to survivors. Non-survivors exhibited significantly higher median admission plasma glucose (APG) values compared to survivors (210 vs. 166 mg/dL; p = .026). There was no statistically significant difference in median values of (random) plasma C-peptide between non-survivors and survivors (3.55 vs. 3.24 ng/mL; p = .906). A significantly higher percentage of patients with an eGFR < 60 mL/min/1.73 m 2 was observed in the non-survivor group as compared to the survivor group (57.9% vs. 23.6%; p = .006). A multivariate analysis performed by a logistic regression model after adjusting for major confounders (age, sex, body mass index, major comorbidities) showed a significant inverse association between admission eGFR values and risk of in-hospital mortality (OR, 0.956; 95% CI, 0.931-0.983; p = .001). We also found a significant positive association between admission WBC count and risk of in-hospital mortality (OR, 1.210; 95% CI, 1.043–1.404; p = .011). Conclusions: Admission eGFR and WBC count predict in-hospital COVID-19 mortality among T2DM patients, independently of traditional risk factors, APG and random plasma C-peptide. Hospitalized patients with COVID-19 and comorbid T2DM associated with impaired kidney function at admission should be considered at high risk for adverse outcomes and death.